Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2001
DOI: 10.2165/00128072-200103030-00002
|View full text |Cite
|
Sign up to set email alerts
|

Aetiology and Management of Children With Acute Fever of Unknown Origin

Abstract: This is part I of a 2-part paper on fever of unknown origin (FUO) in children. FUO is best defined as fever without obvious source on initial clinical examination and then classified into acute (illness of < or =1 week's duration) and prolonged (>7 to 10 days' duration). Aetiologically, there is a marked overlap between acute and prolonged FUO, and infections are major players in both. Age, climate, local epidemiology and host factors are the major aetiological factors that should be considered in the choice o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 173 publications
(393 reference statements)
2
12
0
2
Order By: Relevance
“…Despite a comprehensive examination and exhaustive workup in hospital, FUO remains a diagnostic and therapeutic challenge to expert physicians [2], [7], [8]. The three most common aetiological categories of FUO in children in order of frequency are infectious diseases, connective tissue diseases, and neoplasms [7].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite a comprehensive examination and exhaustive workup in hospital, FUO remains a diagnostic and therapeutic challenge to expert physicians [2], [7], [8]. The three most common aetiological categories of FUO in children in order of frequency are infectious diseases, connective tissue diseases, and neoplasms [7].…”
Section: Discussionmentioning
confidence: 99%
“…The three most common aetiological categories of FUO in children in order of frequency are infectious diseases, connective tissue diseases, and neoplasms [7]. Numerous studies have reported that a diagnosis is never established in 10∼26% of cases of FUO [2], [7], [15]. We applied the term FUO to patients with a fever >101°F (38.3°C) of at least 8-days' duration, in whom no diagnosis is apparent after an initial outpatient or hospital evaluation that includes a careful history and physical examination and initial laboratory assessment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence was significantly higher in children with previous care; (iii) An unfortunately common tendency of focusing only on prevalent diseases, commonly malaria, in the evaluation of acutely ill children, except where there are obvious signs of other infections. This is accompanied by the equally unfortunate practice of ascribing fever unresponsive to antimalarial drugs to drugresistant malaria or enteric fever in some cases [15,16]; (iv) Coexisting focal infections and malaria acting as red herrings [15,16]. Malaria and focal infections were common initial diagnoses in facility-referred children in this study;…”
Section: Discussionmentioning
confidence: 74%
“…Dengan berkembangnya ilmu pengetahuan dan teknologi di bidang kedokteran, metode diagnostik dalam mendiagnosis penyakit menjadi semakin baik. 1,9,10 Penyakit yang semula sulit didiagnosis saat ini menjadi lebih mudah didiagnosis. Faktor lain adalah lokasi dan tempat tinggal pasien.…”
Section: Pembahasanunclassified